Alternative pathways to carbon mobility - Givoni, M (Edward Elgar, 2013)
Low carbon mobility is defined as mobility that results in substantially lower levels of carbon consumption and emissions. Here, mobility is defined as the total amount of travel that is undertaken on all forms of transport (Chapter 1), and carbon is used to illustrate the various negative environmental impacts from transport (Chapter 11). As discussed in Part I of the book, and emphasized in Chapter 12, it is the nature of the current transport and mobility system that results in high levels of carbon consumption and emissions, with each of the elements of the system as well as the linkages between them acting to preserve or reinforce high carbon mobility. The term ‘pathway’ is commonly used in the futures and transition literature. For example, scenario analysis often involves developing and describing pathways, but there is no single common definition of what a pathway is and usage of the term varies between studies and applications. Geels and Schot (2007) use the term to suggest different ways in which transition might take place (Chapter 14). Foxon et al. (2010) use the notion of pathways to explore how the UK electricity system might evolve if different approaches to managing the sector were applied to achieve a low carbon electricity system.